Histone Deacetylase Inhibitor Alleviates the Neurodegenerative Phenotypes and Histone Dysregulation in Presenilins-Deficient Mice - Cao, Ting; Zhou, Xiaojuan; Zheng, Xianjie; Cui, Yue; Tsien, Joe Z.; Li, Chunxia; Wang, Huimin (Frontiers in Aging Neuroscience, 2018)
Histone acetylation has been shown to play a crucial role in memory formation, and histone deacetylase (HDAC) inhibitor sodium butyrate (NaB) has been demonstrated to improve memory performance and rescue the neurodegeneration of several Alzheimer’s Disease (AD) mouse models. The forebrain presenilin-1 and presenilin-2 conditional double knockout (cDKO) mice showed memory impairment, forebrain degeneration, tau hyperphosphorylation, and inflammation that closely mimics AD-like phenotypes. In this paper, we have investigated the effects of systemic administration of NaB on neurodegenerative phenotypes in cDKO mice. We found that chronic NaB treatment significantly restored contextual memory, but did not alter cued memory in cDKO mice while such an effect was not permanent after treatment withdrawal. We further revealed that NaB treatment did not rescue reduced synaptic numbers and cortical shrinkage in cDKO mice, but significantly increased the neurogenesis in subgranular zone of dentate gyrus. We also observed that tau hyperphosphorylation and inflammation related protein GFAP level were decreased in cDKO mice by NaB. Furthermore, GO and pathway analysis for the RNA-Seq data demonstrated that NaB treatment induced enrichment of transcripts associated with inflammation/immune processes and cytokine-cytokine receptor interactions. RT-PCR confirmed that NaB treatment inhibited the expression of inflammation related genes such as S100a9 and Ccl4 found upregulated in the brain of cDKO mice. Surprisingly, the level of brain histone acetylation in cDKO mice was dramatically increased and was decreased by the administration of NaB, which may reflect dysregulation of histone acetylation underlying memory impairment in cDKO mice. These results shed some lights on the possible molecular mechanisms of HDAC inhibitor in alleviating the neurodegenerative phenotypes of cDKO mice and provide a promising target for treating AD.